Co-ordinating meaning within a gender identity development service: What can the theory of the co-ordinated management of meaning offer clinicians working with young people, and their families, exploring their gender identities. (April 2019) - Miller, Ashley; Davidson, Sarah
Working with young people who present with diverse gender identifications and their families requires consideration and acknowledgement of a range of contexts (including relationship, family, social and cultural) as well as the influences of prior experience and language. Family members often present with diverse understandings and hopes from their referral to the Gender Identity Development Service and look to us to meet these. This article considers the contribution of Cronen and Pearce who introduced the theory of the co-ordinated management of meaning (CMM). We focus on their ideas about communication, the complexities of communication, meaning, context and multiple perspectives. This article relates to our practice as well as considers useful ways to work with families and young people, within a highly contested field. Clinical examples are used to illustrate how we have made use of the theory and models of CMM to facilitate engagement, build therapeutic rapport, facilitate understanding and support those we see in a way which takes into account the many contexts of their lives.